Interactions of monitored factors upon tensile glue shear strength on laser cut wood. (15th February 2020) - Gaff, Milan; Razaei, Fatemeh; Sikora, Adam; Hýsek, Štěpán; Sedlecký, Miroslav; Ditommaso, Gianluca; Corleto, Roberto; Kamboj, Gourav; Sethy, Anil; Vališ, Michal; Řipa, Kamil
Abstract: Over recent decades, laser technology is at the forefront of material processing and in the near future, probably, it can be considered as a replacement for traditional techniques such as sawing. This paper reports the effect of monitor factors (cutting methods, moisture content at laser cutting, surface waviness and roughness) on tensile shear strength of glued layered wood. The process of laser cutting was applied on beech ( Fagus sylvatica L.) and oak wood ( Quercus robur L.). The quality of the surfaces resulted from laser cutting was measured by contact type surface profilometer. To ascertain the bonding behavior, laser cut surfaces were bonded with polyvinyl acetate adhesive and tensile glue shear strength was investigated on the bond-line. The results were compared with the results on saw cut samples. The test results revealed significant influence of monitored factors on the tensile shear strength of glued joints. The tensile glue shear strength values on laser-cut wood samples were significantly lower than those on saw cut samples.